PEMBUATAN Dye (Zat Warna) BERBAHAN DASAR KUBIS MERAH (Brassica Oleracea L.) DENGAN METODE MASERASI - Wardah Nabila Putri; Sherly Kasuma Warda Ningsih (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2025)
DSSC fabrication using expensive and difficult to obtain synthetic dye sensitizers can be overcome by utilizing natural dyes from red cabbage. Dye or dye functions as a compound that absorbs sunlight. This study aims to explore the characteristics of anthocyanin pigments extracted from natural materials, namely red cabbage (Brassica Oleracea) as a dye-sensitizer in Dye Sensitized Solar Cell (DSSC) type solar cells. Anthocyanin pigments were chosen because of their ability to absorb light in a broad spectrum, their environmentally friendly nature, and their abundant availability in nature. Pigment extraction was carried out using 70% ethanol solvent and characterization was carried out using Fourier Transform Infrared Spectroscopy (FTIR) and UV-Visible (UV-Vis). The results of the FTIR analysis showed anthocyanin. UV-Vis analysis showed an absorption peak at a wavelength of 323 nm. The results of this study indicate that anthocyanin pigments from natural materials have the potential as effective and environmentally friendly dye-sensitizers in the development of DSSC